Business Software Human Resource Information System for Assistance Human Capital Performance - Lis Lesmini; Kamsariaty; Devi Marlita; Ni Nyoman Sawitri; Josua Panatap Soehaditama (Formosa Journal of Multidisciplinary Research, 2023)
The purpose of this study is to see from scientific articles about software business on human capital or human resources the influence and results of existing research.  In writing this study, we used a qualitative approach by reviewing the literature on study variables. Literary studies is a type or method of academic writing in the form of library studies.  In accordance with the purpose of the study to see the HRIS software business with the relationship between human capital performance, from the results of the presentation of article literature and discussion researchers concluded that HRIS has been used in almost all organizations by helping Human Capital in working, although there is data that states only 45% are newly used by small community business units but in general from the article literature states that HRIS has been used,  especially to assist the Human resources department in carrying out its functions. The recommendation of researchers from the results of this scientific article is that a literature review is a finding of a phenomenon and gap that is used in this scientific article so as to make an input for other researchers in the future.